Effect of different irradiance levels on bioelectricity generation from algal biophotovoltaic devices / Thong Cheng Han - Thong , Cheng Han (2019)
Photosynthesizing organisms including microalgae are exposed to varying levels of light irradiance throughout the day, thus sparking strong research interests in determining the effects of different irradiance levels on the efficiency of biophotovoltaic (BPV) platforms in generating bioelectricity. When light energy strikes the surface of the photosynthetic apparatus of algal cells, electrons are shuttled from the algal cells to the anode through a mediator but scientific findings have suggested that direct electron transfer from the microalgae to the anode could boost the efficiency of electron transport mechanism in a BPV device by reducing internal resistance (Ng et al., 2014a). In this study, mediator less anodes were adopted in the BPV devices by growing algal biofilms from suspension and immobilized Chlorella sp. (UMACC 313) cultures on ITO-coated glass anodes. Immobilized cultures were prepared by entrapping the microalgal cells in 2% sodium alginate solution. The BPV devices were illuminated by four different irradiance levels (30, 90, 150 and 210 µmol photons m-2 s-1 ) to investigate the relationship between varying irradiance levels on the power output of the devices. Photosynthetic performance of the microalgal cells was evaluated using Pulse Amplitude Modulation Fluorometer (PAM) on Days 0, 4, 8 and 12 of the experiment whereas power output of the BPV devices were found from polarization curves generated by applying external resistance stepping technique (Ng et al., 2017). The maximum power density and maximum current density were produced from alginate-immobilized biofilms at the irradiance level of 150 µmol photons m-2 s-1 . High Non-Photochemical Quenching (NPQ) readings at 150 µmol photons m-2 s-1 indicated effective photoprotection in Photosystem II (PS II) that prevents inactivitation of PS II when exposed to strong irradiance. Thelowest power output from immobilized cultures was recorded at 210 µmol photons m-2 s-1 , thus suggesting that partialphotoinhibition had occurred at high irradiance level